Indigenous knowledge: Going Local - Englberger, Lois; Morens, Adelino (Technical Centre for Agricultural and Rural Cooperation, 2008)
Using television, radio, the web and printed publications, a project in the Pacific island of Pohnpei restores interest in traditional crops and promotes healthy local food.